Is Grace Free? Charts and Christ in Romans in Conversation with John Barclay's Paul and the Gift - Helso, Desta (The Evangelical quarterly, 2018)
This article interacts with John Barclay's Paul and the Gift as it explores the question of whether Paul thought that grace in relation to Christ was free in his epistle to the Christians in Rome. It examines grace in Romans and in the Patristic and Ethiopian interpretative traditions and finds an inextricable connection between the divine gift and the divine giver. Christ himself is the gift. The implications of this Christological focus for the concept of reciprocity are considered.